Sales teams and its impact on the performance of the organizations: a systematic review of the literature (2022)
In this work, 63 scientific articles published between January 2016 and July 2020 are analyzed which address the topic of sales teams of organizations and their relationship with commercial performance, indexed in Scopus and Web Of Science. The methodology established by the Scottish Intercollegiate Guidelines Network was used. The findings indicate the existence of a theoretical and practical body associated with topics such as the characteristics of sellers, sales performance, marketing and leadership, elements that could be appropriated by organizations to improve their benefits. Posts linking marketing, sales teams and their performance were few compared to those associated with salesperson characteristics. In this sense, future works could address the incidence of branding, brand positioning and incentives for marketing and sales teams.